Heroes and Villains: Increasing Fan Involvement in Pursuit of “The Elusive Fan” - Thomas S. Mueller; John C. Sutherland (Journal of Applied Sports Management, 2010)
The sport consumption experience apparently facilitates a higher symbolic meaning, indicating a symbolic communicative role in the social psyche of consumers. Involvement with group members in the social (sport) setting appears to influence attendees’ self-concept. Despite a postmodern shift to individuality, Americans still choose to exist within the parameters of collective traditions and within communities of shared interests through the social institution of sport (Bellah, 1985). According to Rein et al. (2006), one of seven vital way sport properties can attract/retain such elusive fans involves heightening their attractions to the properties by emphasizing rivalries, which, in turn, increases fan involvement. Rivalries create the foundation for story lines that ingratiate the sport fan and consumer to one team or athlete over another. Sport administrators, event managers, and sport product marketers can observe fan response to heroes and villains to frame promotional campaigns, use them to heighten fan interest, and thus better connect with fans in a crowded marketplace. The purpose of this research was to gain insight into fan perceptions of heroes and villains within team sport, specifically the sport of American football played in the National Football League (NFL) and National Collegiate Athletic Association (NCAA), through a pilot test designed to determine the feasibility of a larger study.
Keywords: Sports fans; Game attendance; Sport viewership; Fan involvement; College football; NFL football; Sport marketing; Sport media; Sport communication; Sport business; Sponsorship; Heroes; Villains; Rivalries